ANALISIS DAMPAK SOSIAL, EKONOMI, DAN PSIKOLOGIS PENDERITA HIV AIDS DI KOTA DENPASAR - Yudi Pardita, Dewa Putu; Sudibia, I Ketut (Buletin Studi Ekonomi, 2016)
The Social, Economic, and Psychological Impacts of  HIV AIDS Sufferers In Denpasar. This study aims to investigate the social, economic, and psychological impacts of HIV AIDS sufferers in Denpasar. Data was collected with accidental sampling of 86 respondents of HIV AIDS sufferers in Denpasar. McNemar test was used to measure the social, economic, and psychological impacts of the respondents before and after being infected with the HIV AIDS disease. The findings of the research indicate that social variables that changes after getting infected are the intensity of the meeting, the intensity of visiting their family or relatives, the intensity of mutual cooperation, and the intensity of attending the invitation of traditional gatherings. The economics variable that changes is only the working hour. The psychological indicators namely stress, frustration, anxiety, anger, denial, shyness, and grief also experienced changes.   Keywords: the economic, psychological, and social impacts, HIV AIDS
Keywords: the economic, psychological, and social impacts, HIV AIDS